Virtual screening and evaluation of bioactive peptides from Haliotis discus hannai as potential HMGCR inhibitors for hyperlipidemia treatment - Qiao, Kun; Liu, Lina; Chen, Yihui; Huang, Qiongmei; Chen, Bei; Wu, Jingna; Huang, Wenmei; Liu, Zhiyu (Frontiers in Nutrition, 2024)
IntroductionHyperlipidemia remains a major disease threatening global public health. The morbidity and mortality associated with cardiovascular diseases have been increasing. The inhibition of 3-Hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR), a key enzyme in the cholesterol synthesis pathway, can effectively reduce cholesterol levels.Methods and resultsIn this study, the most suitable protease for preparing HMGCR inhibitory peptides was screened using the evaluation indexes of peptide yield and HMGCR inhibition rate. Peptide sequences with molecular weights <1 kDa were identified, and peptide fragments were docked with HMGCR for virtual screening. The inhibitory effects of these peptides on HMGCR activity were evaluated in vitro using a high-fat Hep-G2 cell model. The screened peptides possessed significant HMGCR inhibitory activity and reduced cholesterol micelle solubility and total cholesterol and triglyceride levels in hyperlipidemic Hep-G2 cells.ConclusionThis study provides novel insights into developing natural drugs for hyperlipidemia; moreover, the results will facilitate the functional application of marine bioactive peptides.